Association Between Neutralizing Antibody Titers against Parechovirus A3 in Maternal and Cord Blood Pairs and Perinatal Factors. (20th May 2019) - Shimizu, Hiromi; Hashimoto, Koichi; Sato, Maki; Sato, Akiko; Sato, Masatoki; Maeda, Hajime; Kyozuka, Hyo; Kawasaki, Yukihiko; Yokoyama, Tadahiko; Fujimori, Keiya; Yasumura, Seiji; Hosoya, Mitsuaki
Abstract: Background: Parechovirus A3 (PeV-A3) is a pathogen that causes severe infectious diseases such as sepsis and meningoencephalitis in neonates and young infants. In this study, we aimed to measure the neutralizing antibody titer (NAT) against PeV-A3 in paired maternal and cord blood samples and to clarify the serum epidemiology of PeV-A3 and the association between the NAT and perinatal factors. Methods: NATs against PeV-A3 were measured in 1033 mothers (maternal and cord blood pairs; total of 2066 samples) who delivered their infant in Fukushima Prefecture between December 2013 and June 2014. RD-18S cells were used to measure NATs against PeV-A3. The association between NATs against PeV-A3 in maternal and cord blood and perinatal factors was determined using multivariate logistic regression analysis. Results: The median gestational age of the infants was 39 weeks 4 days (interquartile range, 38 weeks 4 days to 40 weeks 3 days). The NATs against PeV-A3 in maternal blood and in cord blood were almost the same. The proportion of samples assigned to the low-titer group (NAT ≤ 1:16) was approximately 70%, and the proportion of samples assigned to the high-titer group tended to increase with gestational age. The high-titer rate and geometric mean titers decreased with increased maternal age. Conclusions: Cord blood indicates that neonates born at a lower gestational age and older mothers have a low NAT against PeV-A3. Thus, more attention should be paid to the onset of severe PeV-A3 disease in such neonates and young infants. Abstract : In this study, we aimed to clarify the serum epidemiology of parechovirus A3 (PeV-A3) infection and to assess its association with perinatal factors. More attention should be paid to the possibility of severe PeV-A3 infection in neonates and young infants born at a lower gestational age and older mothers.